2009
DOI: 10.1007/s00267-009-9406-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Visitor Use in Protected Areas: Future Opportunities in Recreation Ecology Research Based on the USA Experience

Abstract: Recreation ecology, the study of environmental consequences of outdoor recreation activities and their effective management, is a relatively new field of scientific study having emerged over the last 50 years. During this time, numerous studies have improved our understanding of how use-related, environmental and managerial factors affect ecological conditions and processes. Most studies have focused on vegetation and soil responses to recreation-related trampling on trails and recreation sites using indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
140
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(154 citation statements)
references
References 63 publications
1
140
1
12
Order By: Relevance
“…Recreation opportunities can be maximised by the implementation of appropriate management actions including development and maintenance of National Park infrastructure (Niedziałkowski et al, 2014;Rannow et al, 2014;Watson et al, 2014). Many studies have also identified proper trail management as enhancing recreational use of National Parks (Dixon et al, 2004;Hawes et al, 2013;Leung and Marion, 2000;Leung, 2001, 2004;Monz et al, 2010;Pickering et al, 2010). Most of these previous works were related to the overall problem of trail condition and degradation related to their utilization (e.g.…”
Section: Scenario 3 -Trail Degradation and Natural Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recreation opportunities can be maximised by the implementation of appropriate management actions including development and maintenance of National Park infrastructure (Niedziałkowski et al, 2014;Rannow et al, 2014;Watson et al, 2014). Many studies have also identified proper trail management as enhancing recreational use of National Parks (Dixon et al, 2004;Hawes et al, 2013;Leung and Marion, 2000;Leung, 2001, 2004;Monz et al, 2010;Pickering et al, 2010). Most of these previous works were related to the overall problem of trail condition and degradation related to their utilization (e.g.…”
Section: Scenario 3 -Trail Degradation and Natural Restorationmentioning
confidence: 99%
“…These problems have been described from all around the world (e.g. Arrowsmith and Inbakaran, 2002;Ballantyne and Pickering, 2015;Belnap, 1998;Cole, 1993;Dixon et al, 2004;Hill and Pickering, 2006;Marion, 1996, 2000;Marion et al, 1993;Monz et al, 2010;Ólafsdóttir and Runnström, 2013;Özcan et al, 2013;Pickering et al, 2010;Tomczyk, 2011;Tomczyk and Ewertowski, 2013b). Extreme weather events, particularly intense rainfall, have similar adverse effects on trails.…”
Section: Introductionmentioning
confidence: 99%
“…This topic has been the subject of numerous studies, with an extensive overview having been provided by several publications (e.g. Marion, 1996, 2000;Sun and Walsh, 1998;Orams, 2002;Cole, 2004;Davenport and Davenport, 2006;Pstrocka and Rak, 2006;Pickering et al, 2010;Monz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Social carrying capacity of visitors can be framed in terms of visitor standards for certain environmental or social conditions of recreational areas, based on normative theory adapted from social sciences (Manning & Freimund 2004;Manning 2013). This concept is related to the emergence of a new field -recreation ecology, which studies the impacts of outdoor recreation on natural or semi-natural environments and their effective management (Monz et al 2010). Studies on this topic originating from North America represent well comparable and focused research efforts with a long research history.…”
Section: Introductionmentioning
confidence: 99%